The link between absorptive capacity and IT firm performance in Portugal - Mata, Mário Nuno Neves da Silva (2022)
This dissertation comprises three articles as outputs of a broader research project focused on the following study purpose: This research may help Portugal’s IT (Information Technology) industry better understand the importance of collaborative innovation with regard to achieving financial objectives. It could also enhance researchers’ understanding of the relationship between collaborative innovation and intellectual capital regarding attaining and maintaining absorptive capacity. The additional contributions made by research on SME project-based IT Companies in Portugal relate to the way in which potential and realized absorptive capacity enhance project success and strategic agility act as a mediated mechanism and moderator of project complexity. Is there any relationship between customer knowledge management capability, strategic agility, absorptive capacity, financial performance, and collaborative innovation capability? In article 1, the results show that collaborative innovation has a positive and significant impact on the financial performance of Portuguese IT companies. Absorptive capacity is considered a potential mediator between collaborative innovation and financial performance. In article 2, The results indicate that the two sub-dimensions of absorptive capacity, potential and realized absorptive capacity, not only affect a project’s success directly but also indirectly through the mediator of strategic agility. In article 3, The findings demonstrate that collaborative innovation contributes significantly to the financial performance of IT firms in Portugal. The results also indicate that absorptive capacity and strategic agility both positively and significantly affect the relationship between collaborative innovation and a company’s financial performance. Lastly, theoretical and practical contributions are made, and research limitations and future research suggested.